2011
DOI: 10.1007/s11426-011-4286-y
|View full text |Cite
|
Sign up to set email alerts
|

Facile shape and size-controlled growth of uniform magnetite and hematite nanocrystals with tunable properties

Abstract: Monodispersed magnetite Fe 3 O 4 and hematite -Fe 2 O 3 nanocrystals have been grown in co-solvents of alcohol and water. Either the shape or the size of the nanocrystals could be easily controlled. Both the phases and nanostructures have been characterized by powder X-ray diffraction patterns and electron microscopy. The magnetic and catalytic properties of these products were investigated and compared with each other. The obtained results clearly demonstrate that these iron oxide nanocrystals are soft ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
1
3
0
1
Order By: Relevance
“…The specific saturation magnetization significantly increases with a coercive force reduce. For the crystal, the saturation magnetization increases with increasing crystal grain size, but the coercive force decreases [16]. This is consistent with the result of Fig.…”
Section: Resultssupporting
confidence: 92%
“…The specific saturation magnetization significantly increases with a coercive force reduce. For the crystal, the saturation magnetization increases with increasing crystal grain size, but the coercive force decreases [16]. This is consistent with the result of Fig.…”
Section: Resultssupporting
confidence: 92%
“…The weak ferromagnetic behaviour and the effects of shape anisotropy on the magnetic properties have been discussed in our previous paper. 21 Fig. 6c and d shows the magnetic hysteresis loops of the Fe 3 O 4 decahedrons (sample 1#) and octahedrons (sample 3#) at 300 K. It can be found that both of the samples are ferromagnetic despite small coercivities (H c ) and remanent fields (M r ).…”
mentioning
confidence: 95%
“…To deal with the poor lithium ion diffusion in electrode materials which greatly affects the electrochemical performance, many approaches have been employed, such as carbon coating [4][5][6][7][8][9], nanostructure [10][11][12], and modified by electronically conductive phases [13][14][15]. Wan and co-workers [5] synthesized carbon-coated Fe 3 O 4 nanospindles with high reversible capacity (∼745 mAh g −1 at C/5 and ∼600 mAh g −1 at C/2).…”
Section: Introductionmentioning
confidence: 99%